Pengaruh Dua Jenis Perekat Terhadap Briket Arang Tempurung Kelapa - Halim, Abdul; Rante, Milka (Innovative: Journal Of Social Science Research, 2024)
The aim of this study is to determine the impact of coal brick particle dimensions as an alternative energy source. This study uses two types of comparison of coconut coal bricks with three different types of brick size comparison. The method used by observation or observation of calorie values, ash levels, volatilimeters and pressure strength and combustion tests of the briket. The results of the analysis in the study were obtained with the dimensions of briket 0.2 mm, 0.42 mm, 0.5 mm and briket with the highest calorie value is 56.67 cal/g with dimensions 0.5 adhered to kanji, the most value ash content is in coconut coal with an oil glue of 8.96% with dimensions 0.42mm, the maximum volatilimeter is worth 32.71 with oil glues with a size of 0.2 mm, and the strength of the pressure value is at the value of 0.9 gr/cm3. This study found that the differences between the adhesives used in the process of making coconut coal briquettes produced different parameters that influenced the burning rate of the birch.